How do drivers react to partisan bumper stickers? Understanding polarization in apolitical settings - Torres, Rachel Suzanne; Farrer, Benjamin David (Frontiers in Political Science, 2025)
IntroductionThe impact of political polarization is no longer confined to the voting booth, and partisan identity can shape behavior even in seemingly apolitical spaces. In this paper we investigate whether something as simple as seeing a partisan bumper sticker can trigger partisan identity and lead to different driving behavior.MethodsWe use a survey experiment to simulate a variety of realistic encounters with partisan bumper stickers. Specifically, we test drivers’ reactions to both in-party and out-party stickers; to stickers placed on cars being driven well and cars being driven badly; and to stickers placed on cars being driven by people from different demographic groups.ResultsAcross this wide range of scenarios, we find that the presence of an out-partisan bumper sticker makes drivers more likely to react with hostility to bad drivers. While bumper stickers had no effect on how people felt about politics, they did affect how people drove.DiscussionWe conclude that political polarization can escalate the potential for hostility during everyday experiences like driving, and that bumper stickers may be having a bigger impact on road safety than previously thought.